New Orleans’ school meals distribution in response to the COVID-19 pandemic: operational details and geographic coverage - Chaparro, M. Pia; French, Jacob; Creveling, Kristine; Ennin, Naana; Numa, Tiffany; Knapp, Megan (Frontiers in Public Health, 2023)
IIntroduction: To facilitate continuation of school feeding during COVID-19 school lockdowns, U.S. Congress authorized waivers to allow for school meals to be picked up by parents/guardians in non-school settings. We summarized school meals distribution and characterize reach in socially vulnerable neighborhoods in New Orleans, a city prone to environmental disasters, with a city-wide charter school system, and historically high levels of child poverty and food insecurity. Methods: School meals operations data were obtained from New Orleans, Louisiana (NOLA) Public Schools for 3/16/2020-5/31/2020. For each pick-up location, we estimated: average meals available (weekly), average meals served (weekly), number of weeks of operation, and rate of meal pick-up ([meals served/meals available]*100). These characteristics were mapped in QGIS v3.28.3, along with neighborhoods’ Social Vulnerability Index (SVI). Pearson correlation and ANOVA were run to assess differences between operations characteristics and neighborhood SVI. Results: From 38 meal sites, 884,929 meals were available for pick-up; 74% of pick-up sites were in moderately/highly socially vulnerable areas. Correlations between average meals available and served, weeks of operation, rate of meal pick-up, and SVI were weak and not statistically significant. SVI was associated with average rate of meal pick-up but not other operations characteristics. Discussion: Despite the disaggregated nature of the charter school system, NOLA Public Schools successfully pivoted to providing children with pick-up meals due to COVID-19 lockdowns, with 74% of sites located in socially vulnerable neighborhoods. Future studies should describe the types of meals provided to students during COVID-19, in terms of diet quality and nutrient adequacy.